Wineries and agritouristic farms for sustainable development of the territory of the Aeolian Islands - Nicolosi, Agata; Tromby, Francesco; Strazzulla, Marco; Cortese, Lorenzo (Economics of Agriculture, 2018)
The research examines the production and environmental characteristics of the wine producing chain that represent the territorial system of the Aeolian Islands. The aim is to analyze the functional integration between production and agricultural landscape and to suggest some actions for the protection of the area. The research has provided a supply of a questionnaire of knowing several information: general, socio-economic and structural data of farms and entrepreneurs. The Aeolian Islands are a remarkable union between nature, art, traditions that can be exploited in an environmentally sustainable way, avoiding crossing the threshold of the carrying capacity and determining negative externalities that are detrimental to the socio-economic environment.